Early strength type composite foam concrete foaming agent and preparation method thereof

By modifying the composite foaming agent of plant protein, surfactant and nano-alumina ultrafine silica fume, combined with kaolin activator, the problem of insufficient early strength of foam concrete is solved, and the early strength and stability are improved, which is suitable for emergency repair and construction and winter construction projects.

CN120698726AActive Publication Date: 2025-09-26LINYI TIANYUAN CONCRETE ENG CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510954811.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-11
Publication Date
2025-09-26
Estimated Expiration
2045-07-11

AI Technical Summary

Technical Problem

Existing physical foaming agents are difficult to meet the early strength requirements of foam concrete, resulting in extended construction periods, increased costs, and even affecting the safety and durability of engineering structures.

Method used

A composite foaming agent made of modified vegetable protein, surfactants sodium lauryl sulfate and guar gum is used, combined with an early strength agent made of modified nano-alumina and ultrafine silica fume. The foaming multiple and stability are improved through modification treatment, and a metakaolin activator is used to optimize the pore structure and construct an early strength network.

Benefits of technology

It significantly improves the early and long-term strength of foam concrete, improves construction progress and project quality, reduces costs, and realizes a circular economy model of "waste treatment with waste".

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an early strength type composite foam concrete foaming agent and a preparation method thereof, and belongs to the technical field of concrete foaming agents. The concrete foaming agent is prepared from 20-40 parts of a composite foaming agent, 10-15 parts of an early strength agent, 5-10 parts of an activating agent, 0.5-1 part of an organic coagulant, 1-3 parts of a dispersing agent and 70-90 parts of deionized water. The composite foaming agent is prepared by compounding the modified vegetable protein prepared from the peanut shells (agricultural wastes) and the peanut meal (by-products) as raw materials with other raw materials, so that the dependence on a surfactant type foaming agent is reduced, and the foaming multiple is high and the stability is good; the 1-day strength and 28-day strength of the foam concrete are obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete foaming agents, and specifically relates to an early-strength composite foam concrete foaming agent and a preparation method thereof. Background Art

[0002] Foamed concrete utilizes a physical and mechanical foaming process. A foam produced by a foaming agent is added to cement paste or cement mortar, mixed evenly, and poured into various sizes. Curing results in lightweight concrete with numerous closed pores. This concrete boasts lightweight properties, excellent thermal insulation, sound insulation, fire resistance, seismic resistance, and environmental friendliness, and is currently widely used. Foaming agents are a key component of foamed concrete and play a decisive role in its performance. Foaming agents are primarily categorized as chemical and physical based on their foaming mechanism. Physical foaming agents involve mechanically introducing air into the solution through high-speed stirring or compressed air to produce foam. Compared to chemical foaming agents, the process for preparing foamed concrete with physical foaming agents involves pre-preparing the foam, then mixing it with the concrete paste, lightweight aggregate, admixtures, and other materials. Finally, the foamed concrete specimen is cast into a mold and cured. Physical foaming agents are characterized by their long foam lifespan, generally keeping the foam diameter below 1 mm, and maintaining a relatively consistent size. Furthermore, the foam is less likely to break in the concrete slurry, forming large or interconnected pores. Due to their low cost and simple preparation process, physical foaming agents have dominated the relevant research field. Currently, commonly used physical foaming agents are mainly categorized as rosin resin-based foaming agents, surfactant-based foaming agents, protein-based foaming agents, and composite foaming agents.

[0003] However, in practical applications, existing physical foaming agents still have many limitations. Although rosin resin foaming agents have a wide range of raw material sources and are relatively low in cost, their foaming multiple and foam stability are relatively insufficient, making it difficult to meet the needs of some projects with high foam performance requirements. Surfactant foaming agents have strong foaming capabilities, but the uniformity and stability of the foam are greatly affected by environmental factors, and the performance fluctuates significantly under different temperature and humidity conditions. Protein foaming agents have good foam stability, but the raw materials are relatively difficult to obtain, the cost is high, and they are easily affected by microbial erosion, resulting in performance degradation. Composite foaming agents, while combining the advantages of various foaming agents to a certain extent, still need to be improved in terms of early strength performance.

[0004] The early strength of foamed concrete is crucial to construction progress and project quality. In many practical projects, such as emergency repair and construction projects and winter construction projects, foamed concrete is required to reach a certain strength within a relatively short period of time in order to carry out subsequent processes or withstand certain loads. However, the early strength development of foamed concrete prepared by existing physical foaming agents is slow, making it difficult to meet the needs of these special projects, resulting in extended construction periods, increased costs, and even impacts on the safety and durability of engineering structures. Therefore, the preparation of an early-strength composite foamed concrete foaming agent to improve the early strength of foamed concrete while taking into account good foaming performance and stability has become a key issue that needs to be urgently addressed in the current field of foamed concrete technology. Summary of the Invention

[0005] The object of the present invention is to provide an early-strength composite foam concrete foaming agent, which has a high foaming multiple and good foam stability and can significantly improve the early strength of foam concrete.

[0006] In order to achieve the above technical objectives, the technical solution adopted by the present invention is: An early-strength composite foam concrete foaming agent is prepared from the following raw materials in parts by weight: 20-40 parts of a composite foaming agent, 10-15 parts of an early-strength agent, 5-10 parts of an activator, 0.5-1 part of an organic coagulant, 1-3 parts of a dispersant, and 70-90 parts of deionized water; the early-strength agent is a mixture of modified nano-alumina and modified ultrafine silica fume in a mass ratio of 3:1; the composite foaming agent is composed of sodium lauryl sulfate, modified vegetable protein, and guar gum in a mass ratio of 1:(2-3):(0.1-0.3); and the activator is composed of metakaolin and nano-silica in a mass ratio of 5:1.

[0007] Preferably, the modified plant protein is prepared by the following method: (1) Dry the peanut shells and crush them, then pass them through a 60-mesh sieve to obtain peanut shell powder; (2) Peanut shell powder and ethanol were mixed at a solid-liquid ratio of 1:20 g / mL, and ultrasonically treated for 20-40 min and then stirred at 50-70 °C for 2-4 h. After the treatment, the solvent was removed by rotary evaporation, and the obtained product was dried to obtain the peanut shell extract; (3) The peanut meal is dried and crushed to 80 mesh, soaked in sodium bicarbonate solution according to the solid-liquid ratio, magnetically stirred at 50°C for 30-40 minutes, and the wet meal is filtered; (4) Wet meal, water, peanut shell extract, and ferric chloride were added to a reactor in proportion, stirred magnetically at 40°C, and aerated with air for 3-3.5 hours. After the reaction, the pH of the mixture was adjusted to 7.0, and freeze-dried to obtain the modified plant protein.

[0008] Preferably, the ethanol concentration in step (2) is 60-65%.

[0009] Preferably, in step (3), the solid-liquid ratio is 1 g:10 ml, and the mass fraction of the sodium bicarbonate solution is 0.1%.

[0010] Preferably, in step (4), the mass ratio of wet meal to water is 1:5, the amount of peanut shell extract is 0.05-0.1% of the mass of the wet meal, and the mass of ferric chloride is 0.2-0.3% of the mass of the wet meal.

[0011] Preferably, the modified nano-alumina and modified ultrafine silica fume are obtained by modification with silane coupling agent KH550.

[0012] Preferably, the specific surface area of ​​the ultrafine silica fume is ≥15 m² / g, the particle size of nano-alumina is 80-100 nm, and the particle size of nano-silicon dioxide is 10-20 nm.

[0013] Preferably, the organic coagulant is one of triethanolamine, sodium aminoacetate, and disodium edetate.

[0014] Preferably, the dispersant is a polycarboxylic acid dispersant.

[0015] The present invention also provides a method for preparing the above-mentioned early-strength composite foam concrete foaming agent, which comprises the following steps: Step 1: preparing modified vegetable protein and uniformly mixing it with sodium lauryl sulfate and guar gum in a certain proportion to obtain a composite foaming agent; Step 2: Nano-alumina and ultrafine silica fume are respectively dispersed in anhydrous ethanol at a solid-liquid ratio of 1:20, and 3 wt% of silane coupling agent KH550 is added. The mixture is refluxed at 70° C. and stirred for 2 h, centrifuged and washed, and dried at 80° C. to obtain modified nano-alumina and modified ultrafine silica fume. The two are mixed according to a mass ratio to obtain an early strength agent, which is set aside. Step 3: Heat deionized water to 40° C. and add dispersant and organic coagulant in proportion, stirring magnetically and mixing evenly; Step 4: add an activator to the above mixture, stir at 600 rpm for 10 minutes, then add an early strength agent and disperse at high speed at 1200 rpm for 20 minutes, finally add a composite foaming agent and stir at 800 rpm for 15-20 minutes, transfer to a high-pressure homogenizer and circulate homogenize 3 times at a pressure of 35 MPa, and let it stand for 24 hours to obtain an early strength composite foam concrete foaming agent.

[0016] The composite foaming agent of the present invention is prepared by compounding modified plant protein with surfactant sodium lauryl sulfate and guar gum in an appropriate ratio. The modified plant protein utilizes the tannin phenolic hydroxyl groups rich in agricultural waste peanut shell extract to react with peanut meal protein under the catalytic oxidation of ferric chloride to obtain a modified protein product, thereby forming a cross-linked network. 3+ It forms coordination bonds with protein carboxyl / polyphenol hydroxyl groups, and constructs a dual network structure through tannin oxidation cross-linking and metal coordination, which can effectively enhance the foam toughness and stability of protein products; the above-mentioned modified plant protein works synergistically with sodium lauryl sulfate to achieve good foaming effect, and guar gum acts as a thickener to increase foam viscosity and slow down drainage rate. The foaming agent obtained by compounding the three in an optimal ratio improves foaming multiples and stability.

[0017] The early strength agent of the present invention is a compound of nano-alumina obtained by modification with a silane coupling agent and ultrafine silica fume. The silane modification improves its dispersibility in the foaming aqueous solution and its compatibility with organic components, prevents agglomeration, and enhances the interfacial bonding with cement particles. The ultrafine silica fume provides SiO2 with an ultra-high specific surface area, which reacts with Ca(OH)2 to form CSH gel (secondary hydration) in the early stage of cement hydration. The nano-alumina provides a large number of nucleation sites, significantly accelerating the initial hydration reaction of minerals such as C3S and C3A, and promoting the rapid formation of early strength skeletons such as CSH and ettringite (AFt). The two act synergistically to build an early strength network before the cement paste is fully hydrated.

[0018] The metakaolin in the activator has high volcanic ash activity. Its layered structure dissociates in an alkaline environment to release Al and Si, which further participate in early hydration reactions to generate more gels such as CASH, fill pores, refine the pore structure, improve density and early strength, and help reduce later shrinkage; while nano-SiO2 provides an instantaneous silicon source to compensate for lag. The activator achieves dual optimization of porosity and pore size distribution through the particle size design of "nano-compensating micro" and the chemical reaction of "aluminum-silicon mutual promotion", greatly reducing the drying shrinkage of concrete.

[0019] Organic coagulants not only have the traditional function of accelerating coagulant formation, but also can promote the adsorption of nanoparticles on the surface of cement particles and optimize the overlap of hydration products between particles.

[0020] Compared with the existing technology, the beneficial effects of the present invention are: modified plant protein prepared from peanut shells (agricultural waste) and peanut meal (by-product) as raw materials is compounded with other raw materials to form a composite foaming agent, which reduces dependence on surfactant-type foaming agents, has a high foaming multiple and good stability; significantly improves the early (1 day) strength and 28-day strength of foamed concrete; the early strength agent and the activator construct a multi-scale early strength system, and nano-alumina (nano-level) is compounded with ultrafine silica fume (micron-level) to achieve gradient filling from nanometer to micron, and nanoparticles and active minerals fill and refine pores to improve density, which is not only beneficial to early strength, but also significantly improves long-term strength, impermeability and durability; the present invention utilizes kaolin (bauxite tailings), peanut shells and peanut meal to realize a circular economy model of "waste treatment with waste". DETAILED DESCRIPTION

[0021] The technical solution of the present invention will be further described below with reference to specific embodiments, but is not limited thereto.

[0022] Example 1 An early-strength composite foam concrete foaming agent is prepared from the following raw materials in parts by weight: 20 parts of a composite foaming agent, 10 parts of an early-strength agent, 5 parts of an activator, 0.5 parts of an organic coagulant, 1 part of a dispersant, and 70 parts of deionized water; the early-strength agent is a mixture of modified nano-alumina and modified ultrafine silica fume in a mass ratio of 3:1; the composite foaming agent is composed of sodium lauryl sulfate, modified vegetable protein, and guar gum in a mass ratio of 1:2:0.1; and the activator is composed of metakaolin and nano-silica in a mass ratio of 5:1.

[0023] The modified plant protein is prepared by the following method: (1) Dry the peanut shells and crush them, then pass them through a 60-mesh sieve to obtain peanut shell powder; (2) Peanut shell powder was mixed with 60% ethanol at a solid-liquid ratio of 1:20 g / mL, and ultrasonically treated for 20 min and then stirred at 50 °C for 2 h. After the treatment, the solvent was removed by rotary evaporation, and the obtained product was dried to obtain the peanut shell extract. (3) Peanut meal was dried and crushed to 80 mesh, soaked in 0.1% sodium bicarbonate solution at a solid-liquid ratio of 1 g:10 ml, stirred magnetically at 50 °C for 30 min, and the wet meal was filtered; (4) Wet meal, water, peanut shell extract and ferric chloride were added to a reactor in proportion, and the mixture was stirred magnetically at 40°C and aerated with air for 3-3.5 hours. After the reaction, the pH of the mixture was adjusted to 7.0, and freeze-dried to obtain the modified plant protein; the mass ratio of wet meal to water was 1:5, the amount of peanut shell extract was 0.05% of the mass of the wet meal, and the mass of ferric chloride was 0.2% of the mass of the wet meal.

[0024] The modified nano-alumina and modified ultrafine silica fume are both obtained by modification with silane coupling agent KH550.

[0025] The specific surface area of ​​the ultrafine silica fume is ≥15 m² / g, the particle size of nano-alumina is 80 nm, and the particle size of nano-silicon dioxide is 10 nm.

[0026] The organic coagulant is triethanolamine. The dispersant is a polycarboxylic acid dispersant.

[0027] A method for preparing the above-mentioned early-strength composite foam concrete foaming agent comprises the following steps: Step 1: preparing modified vegetable protein and uniformly mixing it with sodium lauryl sulfate and guar gum in a certain proportion to obtain a composite foaming agent; Step 2: Nano-alumina and ultrafine silica fume are respectively dispersed in anhydrous ethanol at a solid-liquid ratio of 1:20, and 3 wt% of silane coupling agent KH550 is added. The mixture is refluxed at 70° C. and stirred for 2 h, centrifuged and washed, and dried at 80° C. to obtain modified nano-alumina and modified ultrafine silica fume. The two are mixed according to a mass ratio to obtain an early strength agent, which is set aside. Step 3: Heat deionized water to 40° C. and add dispersant and organic coagulant in proportion, stirring magnetically and mixing evenly; Step 4: add an activator to the above mixture, stir at 600 rpm for 10 minutes, then add an early strength agent and disperse at high speed at 1200 rpm for 20 minutes, finally add a composite foaming agent and stir at 800 rpm for 15-20 minutes, transfer to a high-pressure homogenizer and circulate homogenize 3 times at a pressure of 35 MPa, and let it stand for 24 hours to obtain an early strength composite foam concrete foaming agent.

[0028] Example 2 An early-strength composite foam concrete foaming agent is prepared from the following raw materials in parts by weight: 40 parts of a composite foaming agent, 15 parts of an early-strength agent, 10 parts of an activator, 1 part of an organic coagulant, 3 parts of a dispersant, and 90 parts of deionized water; the early-strength agent is a mixture of modified nano-alumina and modified ultrafine silica fume in a mass ratio of 3:1; the composite foaming agent is composed of sodium lauryl sulfate, modified vegetable protein, and guar gum in a mass ratio of 1:3:0.3; and the activator is composed of metakaolin and nano-silica in a mass ratio of 5:1.

[0029] The modified plant protein is prepared by the following method: (1) Dry the peanut shells and crush them, then pass them through a 60-mesh sieve to obtain peanut shell powder; (2) Peanut shell powder was mixed with 65% ethanol at a solid-liquid ratio of 1:20 g / mL, and ultrasonically treated for 40 min and then stirred at 70 °C for 4 h. After the treatment, the solvent was removed by rotary evaporation, and the obtained product was dried to obtain the peanut shell extract. (3) Peanut meal was dried and crushed to 80 mesh, soaked in 0.1% sodium bicarbonate solution at a solid-liquid ratio of 1 g:10 ml, stirred magnetically at 50 °C for 40 min, and the wet meal was filtered; (4) Wet meal, water, peanut shell extract and ferric chloride were added to a reactor in proportion, and the mixture was stirred magnetically at 40°C and aerated with air for 3-3.5 hours. After the reaction, the pH of the mixture was adjusted to 7.0, and the mixture was freeze-dried to obtain the modified plant protein; the mass ratio of wet meal to water was 1:5, the amount of peanut shell extract was 0.1% of the mass of the wet meal, and the mass of ferric chloride was 0.3% of the mass of the wet meal.

[0030] The modified nano-alumina and modified ultrafine silica fume are both obtained by modification with silane coupling agent KH550.

[0031] The specific surface area of ​​the ultrafine silica fume is ≥15 m² / g, the particle size of nano-alumina is 100 nm, and the particle size of nano-silicon dioxide is 20 nm.

[0032] The organic coagulant is sodium aminoacetate; and the dispersant is a polycarboxylic acid dispersant.

[0033] A method for preparing the above-mentioned early-strength composite foam concrete foaming agent comprises the following steps: Step 1: preparing modified vegetable protein and uniformly mixing it with sodium lauryl sulfate and guar gum in a certain proportion to obtain a composite foaming agent; Step 2: Nano-alumina and ultrafine silica fume are respectively dispersed in anhydrous ethanol at a solid-liquid ratio of 1:20, and 3 wt% of silane coupling agent KH550 is added. The mixture is refluxed at 70° C. and stirred for 2 h, centrifuged and washed, and dried at 80° C. to obtain modified nano-alumina and modified ultrafine silica fume. The two are mixed according to a mass ratio to obtain an early strength agent, which is set aside. Step 3: Heat deionized water to 40° C. and add dispersant and organic coagulant in proportion, stirring magnetically and mixing evenly; Step 4: add an activator to the above mixture, stir at 600 rpm for 10 minutes, then add an early strength agent and disperse at high speed at 1200 rpm for 20 minutes, finally add a composite foaming agent and stir at 800 rpm for 15-20 minutes, transfer to a high-pressure homogenizer and circulate homogenize 3 times at a pressure of 35 MPa, and let it stand for 24 hours to obtain an early strength composite foam concrete foaming agent.

[0034] Example 3 An early-strength composite foam concrete foaming agent is prepared from the following raw materials in parts by weight: 30 parts of a composite foaming agent, 12 parts of an early-strength agent, 8 parts of an activator, 0.8 parts of an organic coagulant, 2 parts of a dispersant, and 80 parts of deionized water; the early-strength agent is a mixture of modified nano-alumina and modified ultrafine silica fume in a mass ratio of 3:1; the composite foaming agent is composed of sodium lauryl sulfate, modified vegetable protein, and guar gum in a mass ratio of 1:2.5:0.2; and the activator is composed of metakaolin and nano-silica in a mass ratio of 5:1.

[0035] The modified plant protein is prepared by the following method: (1) Dry the peanut shells and crush them, then pass them through a 60-mesh sieve to obtain peanut shell powder; (2) Peanut shell powder was mixed with 65% ethanol at a solid-liquid ratio of 1:20 g / mL, and ultrasonically treated for 40 min and then stirred at 60 °C for 3 h. After the treatment, the solvent was removed by rotary evaporation, and the obtained product was dried to obtain the peanut shell extract. (3) Peanut meal was dried and crushed to 80 mesh, soaked in 0.1% sodium bicarbonate solution at a solid-liquid ratio of 1 g:10 ml, stirred magnetically at 50 °C for 40 min, and the wet meal was filtered; (4) Wet meal, water, peanut shell extract and ferric chloride were added to a reactor in proportion, and the mixture was stirred magnetically at 40°C and aerated with air for 3-3.5 hours. After the reaction, the pH of the mixture was adjusted to 7.0, and the mixture was freeze-dried to obtain the modified plant protein; the mass ratio of wet meal to water was 1:5, the amount of peanut shell extract was 0.08% of the mass of the wet meal, and the mass of ferric chloride was 0.25% of the mass of the wet meal.

[0036] The modified nano-alumina and modified ultrafine silica fume are both obtained by modification with silane coupling agent KH550.

[0037] The specific surface area of ​​the ultrafine silica fume is ≥15 m² / g, the particle size of nano-alumina is 90 nm, and the particle size of nano-silicon dioxide is 20 nm.

[0038] The organic coagulant is disodium ethylenediaminetetraacetate. The dispersant is a polycarboxylic acid dispersant.

[0039] A method for preparing the above-mentioned early-strength composite foam concrete foaming agent comprises the following steps: Step 1: preparing modified vegetable protein and uniformly mixing it with sodium lauryl sulfate and guar gum in a certain proportion to obtain a composite foaming agent; Step 2: Nano-alumina and ultrafine silica fume are respectively dispersed in anhydrous ethanol at a solid-liquid ratio of 1:20, and 3 wt% of silane coupling agent KH550 is added. The mixture is refluxed at 70° C. and stirred for 2 h, centrifuged and washed, and dried at 80° C. to obtain modified nano-alumina and modified ultrafine silica fume. The two are mixed according to a mass ratio to obtain an early strength agent, which is set aside. Step 3: Heat deionized water to 40° C. and add dispersant and organic coagulant in proportion, stirring magnetically and mixing evenly; Step 4: add an activator to the above mixture, stir at 600 rpm for 10 minutes, then add an early strength agent and disperse at high speed at 1200 rpm for 20 minutes, finally add a composite foaming agent and stir at 800 rpm for 15-20 minutes, transfer to a high-pressure homogenizer and circulate homogenize 3 times at a pressure of 35 MPa, and let it stand for 24 hours to obtain an early strength composite foam concrete foaming agent.

[0040] Comparative Example 1 An early-strength composite foam concrete foaming agent, whose raw material composition and preparation method are basically the same as those in Example 1, except that peanut meal is used instead of modified vegetable protein.

[0041] Comparative Example 2 An early-strength composite foam concrete foaming agent, whose raw material composition and preparation method are the same as those in Example 1, except that: the composite foaming agent is composed of sodium lauryl sulfate, modified vegetable protein, and guar gum in a mass ratio of 1:1:0.1.

[0042] Comparative Example 3 An early-strength composite foam concrete foaming agent, whose raw material composition and preparation method are the same as those in Example 1, except that: the composite foaming agent is composed of sodium lauryl sulfate, modified vegetable protein, and guar gum in a mass ratio of 1:1:0.5.

[0043] Comparative Example 4 An early-strength composite foam concrete foaming agent, whose raw material composition and preparation method are the same as those in Example 1, except that: the activator is composed of metakaolin and nano-silicon dioxide in a mass ratio of 4:1.

[0044] Comparative Example 5 An early-strength composite foam concrete foaming agent, whose raw material composition and preparation method are the same as those in Example 1, except that: the activator is composed of metakaolin and nano-silicon dioxide in a mass ratio of 6:1.

[0045] Performance Testing The foaming agents obtained in Examples 1-3 and Comparative Examples 1-5 were used to prepare foamed concrete (cement: water: foaming agent = 1:0.5:0.02) according to the same process. The foaming multiple, water bleeding, and settlement distance of the foaming agent were measured according to the test methods and requirements in the standard JG / T266-2011 "Foamed Concrete". The test results are shown in Table 1 below.

[0046] Table 1 Test results The results in Table 1 above demonstrate that the foaming agents prepared in Examples 1-3 of the present invention exhibit high foaming multiples, excellent foam stability, and significantly improve the early strength of foamed concrete, achieving significantly better results than those in Comparative Examples 1-5. Settlement distance and water exudation are important indicators of foam stability. Examples 1-3 all exhibited relatively low settling distances and relatively low water exudation, demonstrating excellent foam stability. In contrast, Comparative Examples 1-5 exhibited generally higher settling distances and water exudation, particularly Comparative Example 1, which achieved a settling distance of 18.5 mm and a water exudation of 85 ml, indicating poor foam stability. This is due to the dual network (crosslinking + coordination bonds) of the modified plant protein employed in the present invention, which significantly enhances foam toughness; the thickening effect of guar gum inhibits foam breakage; and the synergistic effect of these components optimizes foaming performance. The foaming agent formulation of the present invention effectively maintains foam stability, minimizing foam breakage and liquid precipitation. The one-day and 28-day compressive strengths of Examples 1-3 were also significantly higher than those of Comparative Examples 1-5. This is due to the synergistic effect of the optimally proportioned early strength agent and activator, which optimized the structure and density of the cement hydration product. Changing the composition and proportion of the raw materials weakened the corresponding effects.

[0047] The present invention's early-strength composite foam concrete foaming agent significantly improves the foaming multiple and foam stability by optimizing the formula of the composite foaming agent, early-strength agent, and activator, while also significantly increasing the early and long-term strength of the foamed concrete. These advantages make the present foaming agent have broad application prospects in the field of foamed concrete, and are particularly suitable for emergency repair and construction projects and winter construction projects with high requirements for construction progress and project quality.

[0048] It should be noted that the above embodiments are only some of the preferred embodiments of the present invention, and not all of them. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work should fall within the scope of protection of the present invention.

Claims

1. An early-strength composite foam concrete foaming agent, characterized in that: The invention is prepared from the following raw materials in parts by weight: 20-40 parts of a composite foaming agent, 10-15 parts of an early strength agent, 5-10 parts of an activator, 0.5-1 parts of an organic coagulant, 1-3 parts of a dispersant, and 70-90 parts of deionized water; the early strength agent is a mixture of modified nano-alumina and modified ultrafine silica fume in a mass ratio of 3:1; the composite foaming agent is composed of sodium lauryl sulfate, modified vegetable protein, and guar gum in a mass ratio of 1:(2-3):(0.1-0.3); and the activator is composed of metakaolin and nano-silica in a mass ratio of 5:

1.

2. The early-strength composite foam concrete foaming agent according to claim 1, characterized in that The modified plant protein is prepared by the following method: (1) Dry the peanut shells and crush them, then pass them through a 60-mesh sieve to obtain peanut shell powder; (2) Peanut shell powder and ethanol were mixed at a solid-liquid ratio of 1:20 g / mL, and ultrasonically treated for 20-40 min and then stirred at 50-70 °C for 2-4 h. After the treatment, the solvent was removed by rotary evaporation, and the obtained product was dried to obtain the peanut shell extract; (3) The peanut meal is dried and crushed to 80 mesh, soaked in sodium bicarbonate solution according to the solid-liquid ratio, magnetically stirred at 50°C for 30-40 minutes, and the wet meal is filtered; (4) Wet meal, water, peanut shell extract, and ferric chloride were added to a reactor in proportion, stirred magnetically at 40°C, and aerated with air for 3-3.5 hours. After the reaction, the pH of the mixture was adjusted to 7.0, and freeze-dried to obtain the modified plant protein.

3. The early-strength composite foam concrete foaming agent according to claim 2, characterized in that The ethanol concentration in step (2) is 60-65%.

4. The early-strength composite foam concrete foaming agent according to claim 2, characterized in that In step (3), the solid-liquid ratio is 1 g:10 ml, and the mass fraction of the sodium bicarbonate solution is 0.1%.

5. The early-strength composite foam concrete foaming agent according to claim 2, characterized in that In step (4), the mass ratio of wet meal to water is 1:5, the amount of peanut shell extract is 0.05-0.1% of the mass of the wet meal, and the mass of ferric chloride is 0.2-0.3% of the mass of the wet meal.

6. The early-strength composite foam concrete foaming agent according to claim 1, characterized in that The modified nano-alumina and modified ultrafine silica fume are both obtained by modification with silane coupling agent KH550.

7. The early-strength composite foam concrete foaming agent according to claim 1, characterized in that The specific surface area of ​​the ultrafine silica fume is ≥15 m² / g, the particle size of nano-alumina is 80-100 nm, and the particle size of nano-silicon dioxide is 10-20 nm.

8. The early-strength composite foam concrete foaming agent according to claim 1, characterized in that The organic coagulant is one of triethanolamine, sodium aminoacetate, and disodium edetate.

9. The early-strength composite foam concrete foaming agent according to claim 1, characterized in that The dispersant is a polycarboxylic acid dispersant.

10. A method for preparing the early-strength composite foam concrete foaming agent according to any one of claims 1 to 9, characterized in that: It includes the following steps: Step 1: preparing modified vegetable protein and uniformly mixing it with sodium lauryl sulfate and guar gum in a certain proportion to obtain a composite foaming agent; Step 2: Nano-alumina and ultrafine silica fume are respectively dispersed in anhydrous ethanol at a solid-liquid ratio of 1:20, and 3 wt% of silane coupling agent KH550 is added. The mixture is refluxed at 70° C. and stirred for 2 h, centrifuged and washed, and dried at 80° C. to obtain modified nano-alumina and modified ultrafine silica fume. The two are mixed according to a mass ratio to obtain an early strength agent, which is set aside. Step 3: Heat deionized water to 40° C. and add dispersant and organic coagulant in proportion, stirring magnetically and mixing evenly; Step 4: add an activator to the above mixture, stir at 600 rpm for 10 minutes, then add an early strength agent and disperse at high speed at 1200 rpm for 20 minutes, finally add a composite foaming agent and stir at 800 rpm for 15-20 minutes, transfer to a high-pressure homogenizer and circulate homogenize 3 times at a pressure of 35 MPa, and let it stand for 24 hours to obtain an early strength composite foam concrete foaming agent.

Citation Information

Patent Citations

  • Three-phase foaming agent, alkali-activated foam concrete and preparation method

    CN117902850A

  • Lightweight foam concrete

    CN117964305A

  • Polymer lightweight concrete foaming agent and preparation method thereof

    CN118420263A

  • Lightweight high-strength foam concrete and preparation method thereof

    CN118459173A

  • Cast-in-place foam concrete preparation method and foam concrete

    CN120157509A